A regional scale gravity survey of the Southern Cross Greenstone Belt, Western Australia - Rout, D.; Dentith, M.; Featherstone, Will (CSIRO Publishing, 1995)
A case study is presented from the Southern Cross Greenstone Belt, Western Australia, where regional scale gravity data have been collected in order to study the belt and associated granitoid bodies. Differential Global Positioning System (GPS) satellite surveying techniques have been used to coordinate the gravity observations, and automated processing techniques, such as terrain corrections based on digital elevation models (DEMs), have been used as part of the study. These approaches greatly reduce the manual effort and time needed to collect and process the gravity data. While the use of GPS methods introduces further considerations in data reduction, such as the geoid-spheroid separation, it can provide up to a 250% increase in efficiency in the field while collecting survey data. The computer based terrain correction calculation using a DEM provides a considerable saving in the time expended on data reduction. With the introduction of such field practices and reduction methods, gravity as a semi-regional scale exploration tool is becoming more attractive. The present study has shown that station spacings of 1 km should be considered a maximum when working on the semi-regional scale (50?60 km square areas), with closer station spacings (500 m maximum) more appropriate close to expected geological contacts.